(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The aim of the study was to assess heart rate variability (HRV) in pregnant women with threatened miscarriage (TM) as a marker of autonomic maladaptation and a predictor of adverse gestational outcomes. Seventy-two pregnant women at 8–22 weeks of gestation were examined: 42 patients with clinical signs of TM and 30 women with physiological pregnancy. HRV was recorded by 5-minute cardiointervalography. Patients with TM demonstrated a significant decrease in SDNN, RMSSD, HF, and pNN50 with a simultaneous increase in the LF/HF index, reflecting predominance of sympathetic activation and suppression of vagal control. HRV may be considered an accessible and informative method for early identification of pregnant women at high risk.